Magnetic field regulation of mouse bone marrow mesenchymal stem cell behaviours on TiO2 nanotubes via surface potential mediated by Terfenol‐D/P(VDF‐TrFE) film - Haisheng Qi; Qi Ke; Qiwen Tang; Lei Yin; Lixin Yang; Chengyun Ning; Jianyu Su; Liming Fang (Biosurface and Biotribology, 2022)
Abstract It is challenging to match the mutual interactions between implant and host because the biomaterials usually cannot actively adjust their performance to the changing microenvironment. Surface potential is one of the critical factors affecting the bioactivity of biomaterials, but it is difficult to be directly controlled in vivo. Magnetic stimulation has attracted much attention due to its deep penetrability, good reliability, and convenient operability. Here, titanium dioxide (TiO2) nanotubes and Terfenol‐D/P(VDF‐TrFE) composite film are prepared by anodic oxidation and solution casting methods on opposite sides of a titanium sheet, respectively. Terfenol‐D magnetostrictive microparticles deform under a magnetic field, generating surface potential on the P(VDF‐TrFE) piezoelectric matrix through magneto‐electric coupling. Correspondingly, equal opposite charges are induced on the surface of TiO2 nanotubes. Stem cells cultured on TiO2 nanotubes show that cell adhesion, proliferation, and differentiation abilities can be regulated by magnetic strength, which correlates with the absorption of charged proteins. Therefore, a cascade coupling of magnetic, mechanical, electric, biochemical, and cellular effects is established. This work demonstrates the feasibility of regulating the bioactivity of biomaterials in vivo through a magnetic field.